Unraveling the Complex Hybrid Ancestry and Domestication History of Cultivated Strawberry. (28th January 2021) - Hardigan, Michael A; Lorant, Anne; Pincot, Dominique D A; Feldmann, Mitchell J; Famula, Randi A; Acharya, Charlotte B; Lee, Seonghee; Verma, Sujeet; Whitaker, Vance M; Bassil, Nahla; Zurn, Jason; Cole, Glenn S; et al.
Abstract: Cultivated strawberry ( Fragaria × ananassa ) is one of our youngest domesticates, originating in early eighteenth-century Europe from spontaneous hybrids between wild allo-octoploid species ( Fragaria chiloensis and Fragaria virginiana ). The improvement of horticultural traits by 300 years of breeding has enabled the global expansion of strawberry production. Here, we describe the genomic history of strawberry domestication from the earliest hybrids to modern cultivars. We observed a significant increase in heterozygosity among interspecific hybrids and a decrease in heterozygosity among domesticated descendants of those hybrids. Selective sweeps were found across the genome in early and modern phases of domestication—59–76% of the selectively swept genes originated in the three less dominant ancestral subgenomes. Contrary to the tenet that genetic diversity is limited in cultivated strawberry, we found that the octoploid species harbor massive allelic diversity and that F. × ananassa harbors as much allelic diversity as either wild founder. We identified 41.8 M subgenome-specific DNA variants among resequenced wild and domesticated individuals. Strikingly, 98% of common alleles and 73% of total alleles were shared between wild and domesticated populations. Moreover, genome-wide estimates of nucleotide diversity were virtually identical in F. chiloensis, F. virginiana, and F. × ananassa (π = 0.0059–0.0060). We found, however, that nucleotide diversity and heterozygosity were significantly lower in modern F. × ananassa populations that have experienced significant genetic gains and have produced numerous agriculturally important cultivars.